Hiring new key inventors to improve firms' post-M&A inventive output - M. F. Arroyabe; Katrin Hussinger; John Hagedoorn (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Although merger and acquisitions (M&As) are acknowledged as an important means to access innovative assets and know-how, firms' inventive output often declines in the post-M&A period. Financial, managerial and organizational constraints related to the M&A event contribute to inventive output declines and inventors' departure. Prior literature treats the acquiring firm as a passive observer of invention declines. This study argues that acquiring firms can take measures by hiring new key inventors. We show that the hiring of new key inventors in the post-M&A period can counteract invention declines in two ways. First, these newly hired inventors are associated with an increase of corporate inventive output after the M&A. Second, they are also associated with an improved inventive output of inventors already working for the acquiring firm. These results suggest that an appropriate hiring policy can counteract declining inventive output of firms in the aftermath of M&As.
Keywords: O34; O32; G34; 330; M&A; post-M&A inventive output; key inventors; KBV